A high-density ivory white ceramic and preparation method thereof

Black materials are made of raw materials such as potassium long stone, pussy soil in ceramic materials, and using specific ivory white enamel and sexual adjustment, combined with burning improvement treatment, solving the color, gloss and abrasion resistance of ceramic materials are difficult to balance The problem realizes the significant improvement of the performance stability and use efficiency of ceramic products under various conditions.

CN118954954BActive Publication Date: 2025-01-24FUJIAN DEHUA CHENGYI CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411433008.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-24
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The color, gloss and wear resistance of existing ceramic materials are difficult to balance and improve, and performance stability is reduced under scrubbing and high humidity and heat conditions.

Method used

Potassium feldspar, bentonite, zirconia, pyrophyllite and modified additives are used to blend the blank, and the green body is formed by wet ball milling and pressing. High-density ivory white ceramics are prepared using ivory white glaze prepared with albite, quartz, silica, zinc oxide and kaolin, combined with adjustment and calcination improvements.

Benefits of technology

It achieves a balanced improvement between the color, gloss performance and wear resistance of ceramic products, maintains performance stability under scrubbing and high humidity and heat conditions, and significantly improves use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the field of ceramic technology, and in particular to a high-density ivory white ceramic and a preparation method thereof, comprising the following steps: preparing a blank; wet-milling the blank and water according to a weight ratio of 5:2 to obtain a ball mill; pressing the ball mill into a mold to form a blank; wet-milling all raw materials of ivory white glaze to obtain a glaze; applying the glaze to the blank to obtain a glaze body; spraying a property adjuster until the glaze body is wet, and then calcining and improving the treatment to obtain a high-density ivory white ceramic. The ceramic prepared by the present invention has an ivory white color and excellent color. The comprehensive performance effect of the blank is enhanced by the synergistic effect of the raw materials, and the property adjuster is sprayed until the glaze body is wet, and then calcining and improving the treatment to obtain a ceramic body. The obtained ceramic product has improved balance in color, gloss performance and wear resistance, and the product has a significant performance stability effect under scrubbing and high humidity and heat conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to high-density ivory white ceramics and a preparation method thereof. Background Art

[0002] Ceramics are materials and products made from clay as the main raw material and various natural minerals through crushing, mixing, molding and calcining. People call objects made of clay and fired at high temperatures in special kilns ceramics, which is a general term for pottery and porcelain. The glazes used in existing ceramic materials have poor color and gloss performance, and the product glazes have poor wear resistance. It is difficult to balance and improve the color, gloss and wear resistance of the products. In addition, the performance stability of the products is reduced under scrubbing and high humidity and heat conditions, which limits the efficiency of product use. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a high-density ivory white ceramic and a preparation method thereof to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution:

[0005] The present invention also provides a method for preparing high-density ivory white ceramics, comprising the following steps:

[0006] Step 1: 20-25 parts of potassium feldspar, 5-10 parts of bentonite, 4-7 parts of zirconium oxide, 5-8 parts of pyrophyllite, and 4-7 parts of a modifying additive are fully blended to obtain a blank;

[0007] Step 2: wet-milling the blank and water in a weight ratio of 5:2, at a ball milling speed of 1000-1500 r / min, for 1 hour to obtain a ball milled material; pressing the ball milled material into a mold to form a blank, at a pressing pressure of 10 MPa, for 20 minutes;

[0008] Step 3: Wet-mill all the raw materials of ivory white glaze at a speed of 1500r / min for 2h to obtain glaze; apply the glaze to the body at a glaze amount of 550g / m 2 , to obtain a glaze body;

[0009] Step 4: Spray the property adjuster until the glaze is moistened, then calcine and improve the treatment to obtain high-density ivory white ceramics.

[0010] Preferably, the ivory glaze comprises the following raw materials in parts by weight:

[0011] 25-30 parts of albite, 4-7 parts of quartz, 4-7 parts of silicon dioxide, 2-5 parts of zinc oxide, 3-5 parts of kaolin.

[0012] Preferably, the specific operation steps of the calcination improvement treatment are:

[0013] The calcination was first carried out at a temperature of 150-170°C for 1 hour, then the temperature was raised to 750°C at a rate of 2-5°C / min, and the temperature was kept at that temperature for 30 minutes. Finally, the temperature was raised to 1300°C at a rate of 1°C / min, and the calcination was continued for 2 hours. After the calcination was completed, the calcination was naturally cooled to room temperature.

[0014] Preferably, the preparation method of the modified additive is:

[0015] S01: irradiating the silicon carbide whisker in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;

[0016] S02: Blending the irradiated silicon carbide whiskers, sodium silicate solution and yttrium oxide in a weight ratio of (5-7):(3-4):2, subjecting them to a primary ball milling treatment, filtering and drying after the ball milling is completed, to obtain a silicon carbide whisker modifier;

[0017] S03: by weight, 3-5 parts of basalt fiber and 1-3 parts of chitosan solution with a mass fraction of 2-5% are added to 5-8 parts of sodium dodecylbenzene sulfonate solution, and then 2-4 parts of hard acid are added to fully blend to obtain a fiber addition solution;

[0018] S04: The silicon carbide whisker modifier and the fiber additive liquid are mixed in a weight ratio of 5:3 and subjected to secondary ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a modified additive.

[0019] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3-6%.

[0020] Preferably, the ball milling speed of the first-level blending ball milling treatment is 1500 r / min, and the ball milling is for 1 hour; the ball milling speed of the second-level blending ball milling treatment is 1000-1200 r / min, and the ball milling is for 2 hours.

[0021] Preferably, the preparation method of the sexual adjustment agent is:

[0022] S11: mixing nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560 in a weight ratio of 2:5:1 to obtain nano-alumina liquid;

[0023] S12: The sex enhancer and nano-alumina liquid are mixed and stirred in a weight ratio of 2:5 to obtain a sex adjuster. The speed of the mixing and stirring is 750-850r / min, and the mixing and stirring time is 45min.

[0024] Preferably, the preparation method of the sexual effect agent is:

[0025] According to weight, 3-5 parts of wollastonite and 1-2 parts of nano-silica sol are added to 4-7 parts of sodium citrate solution, and then 2-4 parts of flaky talc and 1-3 parts of carboxymethyl cellulose are added, and the mixture is ultrasonically treated. After the ultrasonic treatment is terminated, the mixture is filtered and dried to obtain a sex enhancer.

[0026] Preferably, the mass fraction of the sodium citrate solution is 2-5%; the time of the blending ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.

[0027] The invention also provides a high-density ivory white ceramic, which is prepared by the preparation method of the high-density ivory white ceramic.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The ivory glaze of the present invention is prepared by mixing albite, quartz, silicon dioxide, zinc oxide and kaolin. The glaze is applied on the surface of the body to form a glaze layer, which has an ivory white color and excellent color. Potassium feldspar, bentonite, zirconium oxide, pyrophyllite and modified additives are mixed to form the body. The comprehensive performance of the body is enhanced through the synergistic effect of the raw materials. The property adjuster is sprayed on the glaze body to make it wet, and then the ceramic body is obtained through calcination and improvement treatment. The obtained ceramic product has improved balance in color, gloss performance and wear resistance, and the product has significant performance stability under scrubbing and high humidity and heat conditions;

[0030] 2. The modified additive is irradiated in a proton irradiation box through silicon carbide whiskers to optimize the active efficiency of the whiskers, and then the sodium silicate solution and yttrium oxide are blended and coordinated to enhance the coordination effect of the whiskers and the fiber additive liquid. The fiber additive liquid uses basalt fiber as the matrix, and the system performance is strengthened through the fiber needle structure. The chitosan solution with a mass fraction of 2-5%, the sodium dodecylbenzene sulfonate solution and the stearic acid are fully blended and blended. The whisker structure of basalt fiber and silicon carbide whiskers is matched, and the whisker structure is matched with the fiber structure to strengthen the system structure. The performance of the product is further improved, and the overall performance stability of the green product is more excellent.

[0031] 3. The property adjuster is made of nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560. The system interface effect is enhanced by the coordination between the raw materials, and the property adjuster is synergistically prepared by the property effect agent. The obtained property adjuster is reinforced in the glaze, and the glaze layer has excellent density and density, which enhances the color, gloss and wear resistance of the glaze product. The product has a high-density ivory white glaze layer;

[0032] 4. The performance enhancer is made of wollastonite combined with nano-silica sol, sodium citrate solution, flaky talc and carboxymethyl cellulose and ultrasonically treated. The flaky talc system is reinforced with needle-shaped wollastonite and interspersed in the system product to further reinforce the nano-alumina liquid, so that the color, gloss and wear resistance of the product are better coordinated, and the performance stability of the product is further enhanced. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A method for preparing high-density ivory white ceramics in this embodiment comprises the following steps:

[0035] Step 1: 20-25 parts of potassium feldspar, 5-10 parts of bentonite, 4-7 parts of zirconium oxide, 5-8 parts of pyrophyllite, and 4-7 parts of a modifying additive are fully blended to obtain a blank;

[0036] Step 2: wet-milling the blank and water in a weight ratio of 5:2, at a ball milling speed of 1000-1500 r / min, for 1 hour to obtain a ball milled material; pressing the ball milled material into a mold to form a blank, at a pressing pressure of 10 MPa, for 20 minutes;

[0037] Step 3: Wet-mill all the raw materials of ivory white glaze at a speed of 1500r / min for 2h to obtain glaze; apply the glaze to the body at a glaze amount of 550g / m 2 , to obtain a glaze body;

[0038] Step 4: Spray the property adjuster until the glaze is moistened, then calcine and improve the treatment to obtain high-density ivory white ceramics.

[0039] Ivory white glaze comprises the following raw materials in parts by weight:

[0040] 25-30 parts of albite, 4-7 parts of quartz, 4-7 parts of silicon dioxide, 2-5 parts of zinc oxide, 3-5 parts of kaolin.

[0041] The specific operation steps of calcination improvement treatment are:

[0042] The calcination was first carried out at a temperature of 150-170°C for 1 hour, then the temperature was raised to 750°C at a rate of 2-5°C / min, and the temperature was kept at that temperature for 30 minutes. Finally, the temperature was raised to 1300°C at a rate of 1°C / min, and the calcination was continued for 2 hours. After the calcination was completed, the calcination was naturally cooled to room temperature.

[0043] The preparation method of the modified additive is:

[0044] S01: irradiating the silicon carbide whisker in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;

[0045] S02: Blending the irradiated silicon carbide whiskers, sodium silicate solution and yttrium oxide in a weight ratio of (5-7):(3-4):2, subjecting them to a primary ball milling treatment, filtering and drying after the ball milling is completed, to obtain a silicon carbide whisker modifier;

[0046] S03: by weight, 3-5 parts of basalt fiber and 1-3 parts of chitosan solution with a mass fraction of 2-5% are added to 5-8 parts of sodium dodecylbenzene sulfonate solution, and then 2-4 parts of hard acid are added to fully blend to obtain a fiber addition solution;

[0047] S04: The silicon carbide whisker modifier and the fiber additive liquid are mixed in a weight ratio of 5:3 and subjected to secondary ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a modified additive.

[0048] The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3-6%.

[0049] The ball milling speed for the first-level blending treatment is 1500 r / min, and the ball milling is for 1 hour; the ball milling speed for the second-level blending treatment is 1000-1200 r / min, and the ball milling is for 2 hours.

[0050] The preparation method of the sexual adjustment agent is:

[0051] S11: mixing nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560 in a weight ratio of 2:5:1 to obtain nano-alumina liquid;

[0052] S12: The sex enhancer and nano-alumina liquid are mixed and stirred in a weight ratio of 2:5 to obtain a sex adjuster. The speed of the mixing and stirring is 750-850r / min, and the mixing and stirring time is 45min.

[0053] The preparation method of the sexual effect agent is:

[0054] According to weight, 3-5 parts of wollastonite and 1-2 parts of nano-silica sol are added to 4-7 parts of sodium citrate solution, and then 2-4 parts of flaky talc and 1-3 parts of carboxymethyl cellulose are added, and the mixture is ultrasonically treated. After the ultrasonic treatment is terminated, the mixture is filtered and dried to obtain a sex enhancer.

[0055] The mass fraction of the sodium citrate solution is 2-5%; the time of the blending ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.

[0056] This embodiment also provides a high-density ivory white ceramic, which is prepared by the above-mentioned preparation method of the high-density ivory white ceramic.

[0057] Embodiment 1: A method for preparing high-density ivory white ceramics, comprising the following steps:

[0058] Step 1: 20 parts of potassium feldspar, 5 parts of bentonite, 4 parts of zirconium oxide, 5 parts of pyrophyllite and 4 parts of modified additives are fully blended to obtain a blank;

[0059] Step 2: wet-milling the blank and water in a weight ratio of 5:2, at a ball milling speed of 1000 r / min, for 1 hour to obtain a ball milled material; pressing the ball milled material into a mold to form a blank, at a pressing pressure of 10 MPa, for 20 minutes;

[0060] Step 3: Wet-mill all the raw materials of ivory white glaze at a speed of 1500r / min for 2h to obtain glaze; apply the glaze to the body at a glaze amount of 550g / m 2 , to obtain a glaze body;

[0061] Step 4: Spray the property adjuster until the glaze is moistened, then calcine and improve the treatment to obtain high-density ivory white ceramics.

[0062] Ivory white glaze comprises the following raw materials in parts by weight:

[0063] 25 parts albite, 4 parts quartz, 4 parts silica, 2 parts zinc oxide, 3 parts kaolin.

[0064] The specific operation steps of calcination improvement treatment are:

[0065] The calcination was first carried out at 150°C for 1 h, then the temperature was increased to 750°C at a rate of 2°C / min, and kept at this temperature for 30 min. Finally, the temperature was increased to 1300°C at a rate of 1°C / min, and the calcination was continued for 2 h. After the calcination was completed, the calcined sample was naturally cooled to room temperature.

[0066] The preparation method of the modified additive is:

[0067] S01: irradiating the silicon carbide whisker in a proton irradiation box for 5 minutes at an irradiation power of 350W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;

[0068] S02: mixing the irradiated silicon carbide whiskers, sodium silicate solution and yttrium oxide in a weight ratio of 5:3:2 and subjecting them to a primary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a silicon carbide whisker modifier.

[0069] S03: by weight, 3 parts of basalt fiber and 1 part of 2% chitosan solution were added to 5 parts of sodium dodecylbenzene sulfonate solution, and then 2 parts of hard acid were added to fully blend to obtain a fiber addition solution;

[0070] S04: The silicon carbide whisker modifier and the fiber additive liquid are mixed in a weight ratio of 5:3 and subjected to secondary ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a modified additive.

[0071] The mass fraction of the sodium silicate solution is 2%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3%.

[0072] The ball milling speed of the first-level ball milling treatment for blending is 1500 r / min, and the ball milling is for 1 hour; the ball milling speed of the second-level ball milling treatment for blending is 1000 r / min, and the ball milling is for 2 hours.

[0073] The preparation method of the sexual adjustment agent is:

[0074] S11: mixing nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560 in a weight ratio of 2:5:1 to obtain nano-alumina liquid;

[0075] S12: The sex enhancer and nano-alumina liquid are mixed and stirred in a weight ratio of 2:5 to obtain a sex adjuster. The speed of the mixing and stirring is 750 r / min, and the mixing and stirring time is 45 min.

[0076] The preparation method of the sexual effect agent is:

[0077] According to weight, 3 parts of wollastonite and 1 part of nano-silica sol are added to 4 parts of sodium citrate solution, and then 2 parts of flaky talc and 1 part of carboxymethyl cellulose are added, and the mixture is blended and ultrasonically treated. After the ultrasonic treatment is terminated, the mixture is filtered and dried to obtain a sexual enhancer.

[0078] The mass fraction of the sodium citrate solution was 2%; the blending ultrasonic treatment time was 350W, and the ultrasonic time was 20min.

[0079] This embodiment also provides a high-density ivory white ceramic, which is prepared by the above-mentioned preparation method of the high-density ivory white ceramic.

[0080] Embodiment 2: A method for preparing high-density ivory white ceramics, comprising the following steps:

[0081] Step 1: 25 parts of potassium feldspar, 10 parts of bentonite, 7 parts of zirconium oxide, 8 parts of pyrophyllite and 7 parts of modified additives are fully blended to obtain a blank;

[0082] Step 2: wet-milling the blank and water in a weight ratio of 5:2, at a ball milling speed of 1500 r / min, for 1 hour to obtain a ball milled material; pressing the ball milled material into a mold to form a blank, at a pressing pressure of 10 MPa, for 20 minutes;

[0083] Step 3: Wet-mill all the raw materials of ivory white glaze at a speed of 1500r / min for 2h to obtain glaze; apply the glaze to the body at a glaze amount of 550g / m 2 , to obtain a glaze body;

[0084] Step 4: Spray the property adjuster until the glaze is moistened, then calcine and improve the treatment to obtain high-density ivory white ceramics.

[0085] Ivory white glaze comprises the following raw materials in parts by weight:

[0086] 25 parts albite, 4 parts quartz, 4 parts silica, 2 parts zinc oxide, 3 parts kaolin.

[0087] The specific operation steps of calcination improvement treatment are:

[0088] The calcination was first carried out at 1170°C for 1 h, then the temperature was increased to 750°C at a rate of 5°C / min, and kept at this temperature for 30 min. Finally, the temperature was increased to 1300°C at a rate of 1°C / min, and the calcination was continued for 2 h. After the calcination was completed, the steel was naturally cooled to room temperature.

[0089] The preparation method of the modified additive is:

[0090] S01: irradiating the silicon carbide whisker in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;

[0091] S02: mixing the irradiated silicon carbide whiskers, sodium silicate solution and yttrium oxide in a weight ratio of 7:4:2 and subjecting them to a primary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a silicon carbide whisker modifier.

[0092] S03: by weight, 5 parts of basalt fiber and 3 parts of 5% chitosan solution were added to 8 parts of sodium dodecylbenzene sulfonate solution, and then 4 parts of hard acid were added to fully blend to obtain a fiber addition solution;

[0093] S04: The silicon carbide whisker modifier and the fiber additive liquid are mixed in a weight ratio of 5:3 and subjected to secondary ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a modified additive.

[0094] The mass fraction of the sodium silicate solution is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 6%.

[0095] The ball milling speed of the first-level ball milling treatment for blending is 1500 r / min, and the ball milling is for 1 hour; the ball milling speed of the second-level ball milling treatment for blending is 1200 r / min, and the ball milling is for 2 hours.

[0096] The preparation method of the sexual adjustment agent is:

[0097] S11: mixing nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560 in a weight ratio of 2:5:1 to obtain nano-alumina liquid;

[0098] S12: The sex enhancer and nano-alumina liquid are mixed and stirred in a weight ratio of 2:5 to obtain a sex adjuster. The speed of the mixing and stirring is 850 r / min, and the mixing and stirring time is 45 min.

[0099] The preparation method of the sexual effect agent is:

[0100] According to weight, 5 parts of wollastonite and 2 parts of nano-silica sol are added to 7 parts of sodium citrate solution, and then 4 parts of flaky talc and 3 parts of carboxymethyl cellulose are added, and the mixture is ultrasonically treated. After the ultrasonic treatment is terminated, the mixture is filtered and dried to obtain a sexual enhancer.

[0101] The mass fraction of the sodium citrate solution was 5%; the blending ultrasonic treatment time was 400 W, and the ultrasonic time was 30 min.

[0102] This embodiment also provides a high-density ivory white ceramic, which is prepared by the above-mentioned preparation method of the high-density ivory white ceramic.

[0103] Embodiment 3: A method for preparing high-density ivory white ceramics, comprising the following steps:

[0104] Step 1: 22.5 parts of potassium feldspar, 7.5 parts of bentonite, 5.5 parts of zirconium oxide, 6.5 parts of pyrophyllite, and 5.5 parts of a modifying additive are fully blended to obtain a blank;

[0105] Step 2: wet-milling the blank and water in a weight ratio of 5:2, at a ball milling speed of 1250 r / min, for 1 hour to obtain a ball milled material; pressing the ball milled material into a mold to form a blank, at a pressing pressure of 10 MPa, for 20 minutes;

[0106] Step 3: Wet-mill all the raw materials of ivory white glaze at a speed of 1500r / min for 2h to obtain glaze; apply the glaze to the body at a glaze amount of 550g / m 2 , to obtain a glaze body;

[0107] Step 4: Spray the property adjuster until the glaze is moistened, then calcine and improve the treatment to obtain high-density ivory white ceramics.

[0108] Ivory white glaze comprises the following raw materials in parts by weight:

[0109] 25 parts albite, 4 parts quartz, 4 parts silica, 2 parts zinc oxide, 3 parts kaolin.

[0110] The specific operation steps of calcination improvement treatment are:

[0111] The calcination was first carried out at 160°C for 1 h, then heated to 750°C at a rate of 3.5°C / min, kept at this temperature for 30 min, and finally heated to 1300°C at a rate of 1°C / min, and continued to calcine for 2 h. After the calcination was completed, the sample was naturally cooled to room temperature.

[0112] The preparation method of the modified additive is:

[0113] S01: irradiating the silicon carbide whisker in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;

[0114] S02: mixing the irradiated silicon carbide whiskers, sodium silicate solution and yttrium oxide in a weight ratio of 6:3.5:2 and subjecting them to a primary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a silicon carbide whisker modifier.

[0115] S03: by weight, 4 parts of basalt fiber and 2 parts of chitosan solution with a mass fraction of 3.5% were added to 6.5 parts of sodium dodecylbenzene sulfonate solution, and then 3 parts of hard acid were added and blended to obtain a fiber addition solution;

[0116] S04: The silicon carbide whisker modifier and the fiber additive liquid are mixed in a weight ratio of 5:3 and subjected to secondary ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a modified additive.

[0117] The mass fraction of the sodium silicate solution is 3.5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3-6%.

[0118] The ball milling speed of the first-level ball milling treatment for blending is 1500 r / min, and the ball milling is for 1 hour; the ball milling speed of the second-level ball milling treatment for blending is 1100 r / min, and the ball milling is for 2 hours.

[0119] The preparation method of the sexual adjustment agent is:

[0120] S11: mixing nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560 in a weight ratio of 2:5:1 to obtain nano-alumina liquid;

[0121] S12: The sex enhancer and nano-alumina liquid are mixed and stirred in a weight ratio of 2:5 to obtain a sex adjuster. The speed of the mixing and stirring is 800 r / min, and the mixing and stirring time is 45 min.

[0122] The preparation method of the sexual effect agent is:

[0123] According to weight, 4 parts of wollastonite and 1.5 parts of nano-silica sol are added to 5.5 parts of sodium citrate solution, and then 3 parts of flaky talc and 2 parts of carboxymethyl cellulose are added, and the mixture is ultrasonically treated. After the ultrasonic treatment is terminated, the mixture is filtered and dried to obtain a sexual enhancer.

[0124] The mass fraction of the sodium citrate solution was 3.5%; the blending ultrasonic treatment time was 370 W, and the ultrasonic time was 25 min.

[0125] This embodiment also provides a high-density ivory white ceramic, which is prepared by the above-mentioned preparation method of the high-density ivory white ceramic.

[0126] Comparative Example 1:

[0127] The difference from Example 3 is that no modifying additive is added.

[0128] Comparative Example 2:

[0129] The difference from Example 3 is that the silicon carbide whisker modifier is not used in the preparation of the modified additive.

[0130] Comparative Example 3:

[0131] The difference from Example 3 is that the silicon carbide whisker modifier is directly replaced by the silicon carbide whisker raw material.

[0132] Comparative Example 4:

[0133] The difference from Example 3 is that fiber additive liquid treatment is not used in the preparation of the modified additive.

[0134] Comparative Example 5:

[0135] The difference from Example 3 is that basalt fiber and stearic acid are not added to the fiber-adding liquid.

[0136] Comparative Example 6:

[0137] The difference from Example 3 is that no sodium dodecylbenzene sulfonate solution is added to the fiber additive solution, and deionized water is used instead of the chitosan solution.

[0138] Comparative Example 7:

[0139] The difference from Example 3 is that no sexual conditioning agent was added.

[0140] Comparative Example 8:

[0141] The difference from Example 3 is that no nano alumina liquid is added to the property adjustment.

[0142] Comparative Example 9:

[0143] The difference from Example 3 is that the nano alumina liquid is prepared by using nano alumina and deionized water in a weight ratio of 2:5.

[0144] Comparative Example 10:

[0145] The difference from Example 3 is that no sexual effect agent treatment was used.

[0146] The products of Examples 1-3 and Comparative Examples 1-10 were tested under normal conditions, and placed under high heat and humidity conditions of 10% humidity and 65°C for 12 hours, and then scrubbed 10 times with a load of 1N to test the performance stability of the products. The wear resistance test method is: the glaze surface is cut into a circular test block with a diameter of 30mm, and a wear test is performed using a testing machine with a rotation speed of 50r / min and a load of 5N. The wear rate is tested for 1h. The performance measurement results are as follows:

[0147]

[0148] It can be concluded from Examples 1-3 and Comparative Examples 1-10 that the product of Example 3 of the present invention has uniform color and ivory white under normal conditions, and has excellent glossiness and wear resistance. The product has significant performance stability under high heat, high humidity and scrubbing conditions.

[0149] The present invention does not add modifying additives or property adjusters, and the performance of the product has a significant tendency to deteriorate. At the same time, without adding modifying additives, the product's performance stability deteriorates significantly under high heat, high humidity and scrubbing conditions, while without adding property adjusters, the product's performance deteriorates significantly under normal conditions. The use of modifying additives and property adjusters, the two are coordinated and work together, and the product performance effect is most significant;

[0150] The performance of the products tended to deteriorate to varying degrees when the silicon carbide whisker modifier was not used in the preparation of the modified additive, the silicon carbide whisker modifier was directly replaced by the silicon carbide whisker raw material, the fiber additive liquid was not used in the preparation of the modified additive, basalt fiber and stearic acid were not added to the fiber additive liquid, sodium dodecylbenzene sulfonate solution was not added to the fiber additive liquid, and the chitosan solution was replaced by deionized water.

[0151] At the same time, it is found that the performance of the product is more obviously deteriorated when the silicon carbide whisker modifier is not used than when the fiber additive liquid is not used, and the fiber additive liquid and silicon carbide whisker modifier obtained by different methods have a tendency to deteriorate. Only when the product raw material is obtained by the method of the present invention, the product performance effect is most obvious.

[0152] The performance of the products tended to deteriorate when no nano alumina liquid was added to the property adjuster, the nano alumina liquid was prepared with nano alumina and deionized water in a weight ratio of 2:5, and the property adjuster was not treated with property effect agents. In addition, the performance of the products deteriorated more significantly when no property effect agents were used.

[0153] Since the treatment with sexual effect agent obviously deteriorates the product performance, the present invention further explores and treats it.

[0154] Experimental Example 1:

[0155] The only difference from Example 3 is that wollastonite is not added in the preparation of the sexual effect agent.

[0156] Experimental Example 2:

[0157] The only difference from Example 3 is that nano silica sol and carboxymethyl cellulose are not added in the preparation of the sexual effect agent.

[0158] Experimental Example 3:

[0159] The only difference from Example 3 is that no flaky talc was added in the preparation of the sexual effect agent.

[0160] Experimental Example 4:

[0161] The only difference from Example 3 is that the sodium citrate solution is replaced by water.

[0162] The products of Experimental Examples 1-4 were tested under normal conditions, and placed under high heat and humidity conditions of 10% humidity and 65°C for 12 hours, and then scrubbed 10 times with a load of 1N to test the performance stability of the products. The wear resistance test method is: the glaze surface is cut into a circular test block with a diameter of 30mm, and the wear test is carried out using a testing machine with a rotation speed of 50r / min and a load of 5N. The wear rate is tested for 1h. The performance measurement results are as follows:

[0163]

[0164] It can be seen from Experimental Examples 1-4 that no wollastonite or flaky talc was added in the preparation of the sex-effect agent. Among the factors in the preparation of the sex-effect agent, the performance of the product deteriorated significantly. In addition, no nano-silica sol and carboxymethyl cellulose were added, and the sodium citrate solution was replaced by water. The performance of the product showed a trend of deterioration. Only the sex-effect agent obtained by the specific raw materials of the present invention had the most significant performance effect. The technical effect of the present invention could not be achieved by replacing other raw materials.

[0165] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0166] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing high-density ivory white ceramics, characterized in that: The following steps are involved: Step 1: 20-25 parts of potassium feldspar, 5-10 parts of bentonite, 4-7 parts of zirconium oxide, 5-8 parts of pyrophyllite, and 4-7 parts of a modifying additive are fully blended to obtain a blank; Step 2: wet-milling the blank and water in a weight ratio of 5:2, at a ball milling speed of 1000-1500 r / min, for 1 hour to obtain a ball milled material; sending the ball milled material into a mold to be pressed into a blank, at a pressing pressure of 10 MPa, for 20 minutes; Step 3: Wet-mill all the raw materials of ivory white glaze at a speed of 1500r / min for 2h to obtain glaze; apply the glaze to the body at a glaze amount of 550g / m 2 , to obtain a glaze body; Step 4: Spray the property adjuster until the glaze is moistened, and then calcine and improve the treatment to obtain high-density ivory white ceramics; The ivory glaze comprises the following raw materials in parts by weight: 25-30 parts of albite, 4-7 parts of quartz, 4-7 parts of silicon dioxide, 2-5 parts of zinc oxide, 3-5 parts of kaolin; The preparation method of the modified additive is: S01: irradiating the silicon carbide whisker in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed; S02: Blending the irradiated silicon carbide whiskers, sodium silicate solution and yttrium oxide in a weight ratio of (5-7):(3-4):2, subjecting them to a primary ball milling treatment, filtering and drying after the ball milling is completed, to obtain a silicon carbide whisker modifier; S03: by weight, 3-5 parts of basalt fiber and 1-3 parts of chitosan solution with a mass fraction of 2-5% are added to 5-8 parts of sodium dodecylbenzene sulfonate solution, and then 2-4 parts of hard acid are added to fully blend to obtain a fiber addition solution; S04: mixing the silicon carbide whisker modifier and the fiber additive liquid in a weight ratio of 5:3 and subjecting them to secondary ball milling. After the ball milling is completed, washing, filtering and drying are performed to obtain a modified additive. The preparation method of the property adjustment is: S11: mixing nano-alumina, 4% by mass lanthanum chloride solution and silane coupling agent KH560 in a weight ratio of 2:5:1 to obtain nano-alumina liquid; S12: mixing the sex enhancer and nano-alumina liquid in a weight ratio of 2:5 to obtain a sex enhancer, the speed of mixing is 750-850r / min, and the mixing time is 45min; The preparation method of the sexual effect agent is: According to weight, 3-5 parts of wollastonite and 1-2 parts of nano-silica sol are added to 4-7 parts of sodium citrate solution, and then 2-4 parts of flaky talc and 1-3 parts of carboxymethyl cellulose are added, and the mixture is ultrasonically treated. After the ultrasonic treatment is terminated, the mixture is filtered and dried to obtain a sex enhancer.

2. The method for preparing high-density ivory white ceramics according to claim 1, characterized in that: The specific operation steps of calcination improvement treatment are: The calcination was first carried out at a temperature of 150-170°C for 1 hour, then the temperature was raised to 750°C at a rate of 2-5°C / min, and the temperature was kept at that temperature for 30 minutes. Finally, the temperature was raised to 1300°C at a rate of 1°C / min, and the calcination was continued for 2 hours. After the calcination was completed, the calcination was naturally cooled to room temperature.

3. The method for preparing high-density ivory white ceramics according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3-6%.

4. The method for preparing high-density ivory white ceramics according to claim 1, characterized in that: The ball milling speed of the first-level ball milling treatment is 1500r / min, and the ball milling is for 1h; the ball milling speed of the second-level ball milling treatment is 1000-1200r / min, and the ball milling is for 2h.

5. The method for preparing high-density ivory white ceramics according to claim 1, characterized in that: The mass fraction of the sodium citrate solution is 2-5%; the power of the blending ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.

6. A high-density ivory white ceramic prepared by the preparation method of a high-density ivory white ceramic according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation process of pearl white porcelain for daily use

    CN113072365A

  • Ceramic glaze, handicraft ceramic and preparation method of handicraft ceramic

    CN118652050A